The earliest evidence of domestic chickens in the Japanese Archipelago - Eda, Masaki; Izumi, Hiroe; Yoneda, Minoru; Fujita, Saburo (Frontiers in Earth Science, 2023)
The chicken (Gallus gallus domesticus) is the most conventional domestic animal whose main ancestor is the red junglefowl, found in Southeastern Asia and the southern part of China. It is believed that chickens were brought to the Japanese Archipelago through the Korean Peninsula during the Yayoi period, but its exact age is unknown. Based on the sexual dimorphism of morphology, we have pointed out that most of the chickens in the Yayoi period were males and that they were rarely bred in Japan. During the 58th survey of the Karako-Kagi site (Tawaramoto Town, Nara Prefecture), four pieces of immature Phasianidae bone were excavated from a division groove dating from the early middle Yayoi period. In this study, we performed collagen peptide fingerprinting identification and radiocarbon dating of immature Phasianidae bones from the Karako-Kagi site. Consequently, two peptide mass peaks unique to chickens were observed in samples from the immature bones, and it was revealed that the bones were derived from immature chickens. It was also confirmed that the calibrated age of the sample was between the 4th and 3rd century BC, which coincided with the opening age of the division groove. These results suggest that chickens have been successively bred since the beginning of the middle Yayoi period, at least in the Karako-Kagi village. The date was regarded as the lower limit for the introduction of chickens into the Japanese Archipelago, Korean Peninsula, and East Asia.